Hemophagocytic syndrome in a patient with Fanconi anemia and VACTERL association - Borges, Maria Luiza Rocha da Rosa; Moraes, Victor Coentro Torreiro de; Souza, João Lucas Cruz; Leite, Edinalva Pereira; Santos, Neide; Marques-Salles, Terezinha de Jesus (ABCS Health Sciences, 2022)
Introduction: Hemophagocytic syndrome results from hyperactivity of histiocytes and lymphocytes, triggered by infections, mainly viral by cytomegalovirus, Epstein-Barr and herpes. Fanconi anemia (FA) is a rare genetic disease with heterogeneous symptoms common to other diseases such as VACTERL, a disease of unknown etiology in which there are several congenital malformations. The concomitance of Fanconi and VACTERL anemia occurs in 5 to 30% of FA patients. Report: A 14-month-old male infant was admitted to investigate fever, hepatosplenomegaly, and granulopenia. The patient was diagnosed with hemophagocytic syndrome due to hyperferritinemia, bone marrow hemophagocytosis, transaminase elevation, decreased fibrinogen, and cytomegalovirus (CMV) infection confirmed by serology and PCR. The test with mitomycin C (MMC) showed chromosomal fragility. The patient was diagnosed with a VACTERL/FA association for having a clinic and a test compatible with both FA and VACTERL. Conclusion: The VACTERL/FA association is seldom described, but is present in pediatric medical practice. This study presented the main clinical-laboratory aspects and reviewed the main aspects of the concurrence of this pathology.